Os princípios da precaução e da prevenção no meio ambiente laboral : a atuação do Ministério do Trabalho, da Organização Internacional do Trabalho e do cidadão trabalhador - Gonçalves, Gabriela de Andrade Nogueira (2018)
The balanced labor environment is fundamental to guarantee a decent work that provides a decent life for the human being. Throughout the world and Brazil´s historical and normative evolution, it is verified that there is an indissociability between dignity, health, labor and the environment, which leads to the understanding that the labor environment must be healthy and safe, in order to guarantee the right the physical and psychological well-being of the employee. One of the ways to achieve this healthy condition of the environment is through the application of environmental principles of precaution and prevention, whose understanding is quite divergent when it is analyzed the points of view of authors who have studied these legal guides. In this research, it is adopted the position that they are not identical principles, since they differ, among other things, in the topic related to the scientific proof of the damages resulting from something specific. Therefore, the research main objective is to demonstrate the application of the aforementioned principles in the labor environment, based on instruments provided to the State and the worker citizen, which, when put into practices, aim to safeguard the worker´s life. Based on these terms, then, some instruments are discussed, which can be mentioned the Ministry of Labor activities through Labor Inspection, the implementation of the precautionary and preventive programs recommended by the regulatory norms of that institute, such as the Specialized Service in Occupational Health and Safety Engineering, the Occupational Health Medical Control Program and the Prevention of Environmental Risks, as well as the conventions of the International Labour Organization. In addition, Conventions 155, 161 and 187 are addressed, since they deal with the precaution and prevention in the labor scenario in a wider and generic way. Finally, labor citizenship is demonstrated from the performance of the worker not only as a spectator of the decisions of the productive process, but also as an active subject. The proactive nature of the employee is reflected in the denunciations offered to the inspection agency, in his participation at the Internal Commission for the Prevention of Accidents, at the Committee of Workers' Representatives, in trade unions or even, in extreme cases, in an environmental strike. Based on the elaborated dissertation, written using a deductive method and a bibliographic and documentary research technique, with a qualitative approach, it is inferred that the application of the principles in comment, which is effective when applied in an interdisciplinary way, represents a fundamental mechanism in the promotion of a balanced labor environment.